Study of a fixed-bed column in the adsorption of an azo dye from an aqueous medium using a chitosan–glutaraldehyde biosorbent - Jaime López-Cervantes; Dalia I Sánchez-Machado; Reyna G Sánchez-Duarte; Ma A Correa-Murrieta (Adsorption Science & Technology)
A continuous adsorption study in a fixed-bed column was carried out using a chitosan–glutaraldehyde biosorbent for the removal of the textile dye Direct Blue 71 from an aqueous solution. The biosorbent was prepared from shrimp shells and characterized by scanning electron microscopy, X-ray diffraction, and nuclear magnetic resonance spectroscopy. The effects of chitosan–glutaraldehyde bed height (3–12 cm), inlet Direct Blue 71 concentration (15–50 mg l −1 ), and feed flow rate (1–3 ml min −1 ) on the column performance were analyzed. The highest bed capacity of 343.59 mg Direct Blue 71 per gram of chitosan–glutaraldehyde adsorbent was obtained using 1 ml min −1 flow rate, 50 mg l −1 inlet Direct Blue 71 concentration, and 3 cm bed height. The breakthrough curve was analyzed using the Adams–Bohart, Thomas, and bed depth service time mathematical models. The behaviors of the breakthrough curves were defined by the Thomas model at different conditions. The bed depth service time model showed good agreement with the experimental data, and the high values of correlation coefficients (R 2  ≥ 0.9646) obtained indicate the validity of the bed depth service time model for the present column system.